The Development of a Non-Cognitive Instrument to Measure Learning Motivation in Physics Among Students of The Radiology Engineering Program - Samsun, Samsun; Sarifah, Iva; Margono, Gaguk (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to develop a valid and reliable non-cognitive instrument to measure the learning motivation in Physics among students of the Radiology Engineering Program. Learning motivation is one of the psychological factors that influence students' academic achievement. In the context of Physics, which is often considered a difficult subject, learning motivation becomes a key element in overcoming challenges and enhancing understanding. Therefore, it is important to have an instrument that can accurately measure students' learning motivation, especially in relation to Physics material that is highly relevant to the Radiology Engineering field.The instrument developed in this study is based on learning motivation theory, which includes two main dimensions: intrinsic motivation and extrinsic motivation. Research Method The development process of the instrument was carried out through several stages. The first stage was the identification of motivation indicators relevant to these two dimensions. These indicators were then used to construct the instrument blueprint, which was later validated by experts to ensure the alignment of the items with the existing theory. The instrument was then empirically tested on a sample of students to assess its validity and reliability. Data analysis was performed using exploratory factor analysis (EFA) to assess construct validity, that is, whether the instrument accurately measures the dimensions of learning motivation. Additionally, the Cronbach Alpha reliability coefficient was used to measure the instrument's internal consistency, ensuring that the instrument provides consistent results. Research Findings The findings show that the developed instrument has good construct validity, with a total variance explained of 65%, indicating that the instrument can explain most of the variation in students' learning motivation in Physics. Furthermore, the instrument also demonstrates high reliability, with a Cronbach Alpha value of 0.89, indicating excellent internal consistency. Regression analysis shows that learning independence significantly affects concept understanding in Physics, with a value of F(2, 85) = 15.940, p < 0.001. This indicates that students with higher motivation, both intrinsic and extrinsic, tend to have a better understanding of Physics concepts.